PERBEDAAN VARIASI LAMA SIMPAN TELUR AYAM PADA PENYIMPANAN SUHU ALMARI ES DENGAN SUHU KAMAR TERHADAP TOTAL MIKROBA - Idayanti . .; Sri Darmawati; Ulfa Nurullita (JURNAL KESEHATAN, 2009)
Abstract Background; Chicken's Egg is one of animal producl coming from poultry livestock and well-known as food materials with high protein source and many people consume it. Chicken's egg quality can be in Influenced by keeping place, temperature, dampness, dirt at handling technique and eggshell. Egg can be hit by microbe pollution coming from pollution result both direct and indirect contamination. Habit of keeping chicken's egg forfew dalts al room temperature can cause the egg is easy lo be contaminated by microbe, so lhat the egg quality is easy to destroy or decay. Besides il is oflen done of keeping egg in refrigerator, expected the egg will be more durable.This research aim stok now the diffirence of keeping variation long that is0,6, l2, and l8 drys at refrigerator lemperature with room lemperature to total microbe. Method : This research is pure experiment using device of One Group Pretest - Postest. Research object counted 42 chicken's eggfor pretest is 0 day with restaling one egg so it needs 6 eggs, then as postest is 3 keeping treatment (6, 12, and l8 days), 2 measurement of lemperature (refrigerator temperature mean 40C with room temperature mean 290C) and 6 times restating. Independen variable is long save variation and temperature, dependent variable is total mikkrobe, Statistic calculation is done with SPSS l4/3 windows program Version 11 .0 using factorial test or Two Way Anova with d 0,05. Result : Mean total of microbe al refrigerator temperature with room temperature depend on keeping variation long to experience of significant dffirence to lolal microbe, P<0,05 depend on value of p seen there is significant difference al keeping variation long of chicken's egg at refrigerator temperature with room temperature to total microbe. Conclusion : Total microbe al keeping varialion long 0, 6, 12, and 18 days progressively increase signiftcantly both at refrigerator or room temperature